SEJARAH PERKEMBANGAN & URGENSI ALTERNATIF PENYELESAIAN SENGKETA - FATMAWATI, AMANDA; Yusuf, Yusuf; Hapsari, Atik Mani (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2023)
One tries to work anywhere with no hindrances and can compete with their rivals in the competitive environment of today's globalized world. The emergence of disputes is one of the things that often occurs in circumstances like this. Disputes are ingrained in human life. Disputes in everyday life can arise between business partners, family, friends, husband and wife, and so on. A forum whose task is to resolve disputes can be used as a means of dispute resolution. Courts are the official place to settle disputes, while private institutions offer arbitration. Alternative Dispute Settlement (ADR), or Alternative Dispute Settlement (APS) in Indonesian, is the term used to describe out-of-court dispute resolution.